STRATEGI PENGEMBANGAN USAHATANI JAGUNG (Zea Mays L.) DI KABUPATEN KARO, SUMATERA UTARA - Elvin Desi Martauli; Seringena Br Karo; Swati Sembiring (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2023)
Corn (zea mays) is one of the potential food crops aimed at improving the national economy. The increase made in corn production through the suppression of corn imports by the government so that the land for corn development can be utilized. Karo Regency is a corn production center in North Sumatra that has the potential to develop corn farming with a land area of 107,241 ha with a production of 715,940 tons. The purpose of this study was to analyze the corn farming development strategy and the internal and external constraints faced in corn farming activities. The research method used is descriptive method and data collection techniques are carried out using observation, interviews and questionnaires. There are two sub-districts as samples, namely Simpang Empat and Barusjahe Districts. The analysis technique used is descriptive and SWOT analysis. The results of the study indicate that the development strategies that can be carried out in corn farming in Karo Regency are (a) increasing the bargaining power of farmers in the context of industry/traders that impose strict quality requirements; (b) increase productivity to prepare for competition from imported corn products; (c) planning for weather variations to improve the quality of corn produced by farmers; (d) increase the knowledge and capacity of farmers in the context of controlling pests and diseases in maize; (e) reduce corn production costs to reduce fluctuations in production, quality, and price